Ravishing maidens : writing rape in medieval French literature and law - Gravdal, Kathryn ([Philadelphia] : University of Pennsylvania Press, 1991)
In this study of sexual violence and rape in French medieval literature and law, Kathryn Gravdal examines an array of famous works never before analyzed in connection with sexual violence. Gravdal demonstrates the variety of techniques through which medieval discourse made rape acceptable: sometimes through humor and aestheticization, sometimes through the use of social and political themes, but especially through the romanticism of rape scenes.
Introduction: The archaeology of rape in medieval literature and law -- Plotting rape in the female saints' lives -- The poetics of rape law: Chrétien de Troyes's Arthurian romance -- Replaying rape: feudal law on trial in Le Roman de Renart -- The game of rape: sexual violence and social class in the Pastourelle -- The complicity of law and literature.
Includes bibliographical references (pages [145]-187) and index.
English.
Description based on online resource; title from digital title page (viewed on February 21, 2023).
JSTOR
Keywords: French literature -- To 1500 -- History and criticism; Women -- France -- History -- Middle Ages, 500-1500.; Rape -- France -- History -- To 1500.; Women -- Crimes against -- France -- History -- To 1500.; Women and literature -- France -- History -- To 1500.; France -- Social conditions -- 987-1515.; Rape victims in literature; Sex crimes in literature; Rape in literature; Law, Medieval; Women -- Crimes against -- France -- History; Women and literature -- France -- History; Littérature française -- Jusqu'à 1500 -- Histoire et critique; Femmes -- France -- Histoire -- 500-1500 (Moyen Âge); Femmes -- Crimes contre -- France -- Histoire; Femmes et littérature -- France -- Histoire; France -- Conditions sociales -- 987-1515.; Victimes de viol dans la littérature.; Violence sexuelle dans la littérature.; Viol dans la littérature.; Droit médiéval.; LITERARY CRITICISM -- European -- French; French literature; Law, Medieval; Rape; Rape in literature; Rape victims in literature; Sex crimes in literature; Social conditions; Women and literature; Women -- Crimes against; Women -- Middle Ages; France; To 1515; Criticism, interpretation, etc; History